Efforts to Develop Responsibility in Class IX Students Through the Implementation of the Group Discussion Method - Rinda Tambing, Melda; Megawati Tammu, Reisky (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
Responsibility must be owned by every student, including in participating in learning. However, in reality, in class IX of one of the Christian schools in Lampung, it was found that students still lacked responsibility in carrying out their role as students. Efforts that can be made by teachers to develop student character are by applying learning methods, one of which is group discussion. This research aims to describe the implementation of group discussions in developing the responsibility of ninth-grade students. The research method uses descriptive qualitative. The responsibility of grade IX students during learning can be developed through the application of group discussion methods with preparation, discussion, and closing stages. Indicators of student responsibility seen after applying the group discussion method are students actively participating in learning, following the instructions given, cooperating well, and collecting assignments on time. Students are created in the image and likeness of God, and must certainly be responsible to God. Through the application of learning methods, Christian teachers will lead students to be responsible for all their actions, including being responsible to God. Suggestions for further research are to estimate the time used for discussion according to the topic discussed and to examine the application of group discussions on students' cognitive and skill aspects.